Odpowiedź :
Odpowiedź:
[tex]a)\\\\-x^2-3x-2=0\ \ /\cdot(-1)\\\\x^2+3x+2=0\\\\x^2+2x+x+2=0\\\\x(x+2)+x+2=0\\\\(x+2)(x+1)=0\\\\x+2=0\ \ \ \ \vee\ \ \ \ x+1=0\\\\x=-2\ \ \ \ \ \ \vee\ \ \ \ x=-1\\\\\\b)\\\\(2x+4)(3x-1)=0\\\\2x+4=0\ \ \ \ \ \ \ \ \vee\ \ \ \ 3x-1=0\\\\2x=-4\ \ /:2\ \ \ \ \vee\ \ \ \ 3x=1\ \ /:3\\\\x=-2\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=\frac{1}{3}[/tex]
[tex]c)\\\\3x^2-7x+15=0\\\\\Delta=b^2-4ac\\\\\Delta=(-7)^2-4\cdot3\cdot15=49-180=-131\\\\\Delta<0\ \ brak\ \ rozwiazania\\\\\\d)\\\\x^2-8x+16=0\\\\(x-4)^2=0\\\\x-4=0\\\\x=4[/tex]